Studi Tentang Penerimaan dan Penyaluran Zakat pada Yayasan Abulyatama Indonesia - Anisa Wardani Putri; Kristianingsih (Journal of Applied Islamic Economics and Finance, 2024)
Zakat funds should be managed properly and correctly in accordance with applicable Islamic provisions so that there is an even distribution of wealth and the level of welfare of the Indonesian people. Therefore, competent institutions are needed in their fields to take a role in the welfare of the Indonesian people, especially the groups who are recepients of zakat. This study was conducted to find out how the receipt and distribution of zakat managed by Abulyatama Indonesia for the period 2021. The type of research used is a literature study. Collecting research data and journals, reports in the form of files, official websites containing the concepts studied.